2021
DOI: 10.3389/fmicb.2021.648412
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Diversity and Metabolic Potential of Psychrotolerant Arsenic-Metabolizing Microorganisms From a Subarctic Peatland Used for Treatment of Mining-Affected Waters by Culture-Dependent and -Independent Techniques

Abstract: Arsenic contamination in water by natural causes or industrial activities is a major environmental concern, and treatment of contaminated waters is needed to protect water resources and minimize the risk for human health. In mining environments, treatment peatlands are used in the polishing phase of water treatment to remove arsenic (among other contaminants), and peat microorganisms play a crucial role in arsenic removal. The present study assessed culture-independent diversity obtained through metagenomic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 69 publications
(105 reference statements)
1
4
0
Order By: Relevance
“…These results were expected Pseudomonas is a fast-growing, metabolically versatile genus (Jones et al, 2021). In fact, Pseudomonas has been reported in previous studies (Ponce-Soto et al, 2015) for increasing its abundance during enrichment experiments, including in experiments from cold-metal contaminated sites (Ziegelhöfer and Kujala, 2021). Some genera like Corynebacterium or Kocuria, which were relatively high in the environmental samples from sites A and B, had reduced relative abundances in the enrichments.…”
Section: Majority Of Environmental Microorganisms Are Missed By Selec...supporting
confidence: 66%
See 1 more Smart Citation
“…These results were expected Pseudomonas is a fast-growing, metabolically versatile genus (Jones et al, 2021). In fact, Pseudomonas has been reported in previous studies (Ponce-Soto et al, 2015) for increasing its abundance during enrichment experiments, including in experiments from cold-metal contaminated sites (Ziegelhöfer and Kujala, 2021). Some genera like Corynebacterium or Kocuria, which were relatively high in the environmental samples from sites A and B, had reduced relative abundances in the enrichments.…”
Section: Majority Of Environmental Microorganisms Are Missed By Selec...supporting
confidence: 66%
“…In particular, one of the isolates was related to Pseudomonas veronii, a metal tolerant species of this genus, which has been studied for bioremediation (Malla et al, 2018) and whose genome has been found to have the heavy metal resistance gene arsBDR (Morales et al, 2016). Furthermore, As-tolerant Pseudomonas strains have been previously isolated from same location as site C (Ziegelhöfer and Kujala, 2021). However, unlike the strains presented in this study, the previously reported Pseudomonas showed an optimum growth at 20-28°C, implying this might be a different isolated strain as the optimum temperatures for the Pseudomonas presented here was 10°C.…”
Section: New Metal(loid)-tolerance Insights Into Known Environmental ...mentioning
confidence: 99%
“…ANT_H12B exhibited the highest siderophores production when glycolytic substrate (glucose) was used. This finding suggests that the metabolic profiles of psychrotolerant bacteria can differ significantly, even in microorganisms from the similar taxon [ 60 , 61 ]. Pseudomonas strains generally prefer organic acids due to the regulation of catabolic repression and absence of phosphofructokinase, an important enzyme in the glycolytic pathway [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…No metatranscriptomic studies assessing changes in active functions after rewetting and compare to pristine peatlands were found in our literature search, but some have been carried out in natural peatlands (Lin et al 2014 ; Hausmann et al 2019 ). Additionally, other metatranscriptomic analyses have focused so far on Sphagnum associated microbiomes (Ivanova et al 2018 ; Stough et al 2018 ; Dedysh and Ivanova 2019 ; Carrell et al 2022a , b ; Kolton et al 2022 ), arctic peatlands (Tveit et al 2013 , 2014 , 2015 ; Belova et al 2018 ; Dedysh and Ivanova 2019 ; Ziegelhofer and Kujala 2021 ; Bender et al 2021 ) and specific microbial groups such as protists (Geisen et al 2015 ) and Planctomycetes (Ravin et al 2018 ; Ivanova et al 2018 ; Dedysh and Ivanova 2019 ). Additionally, in cases where peat chemical composition cannot be measured, metatranscriptomics could prove helpful as the function of active genes can provide information to some extent regarding what substrate is being used (with the caveat that information in databases used to functionally annotate genes are limited).…”
Section: Potentials Of Molecular Biology Tools In Peatland Researchmentioning
confidence: 99%